2013
DOI: 10.1371/journal.pone.0064095
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Two-Layered Turbid Media for Non-Invasive, Absolute Oximetry in Cerebral and Extracerebral Tissue

Abstract: We introduce a multi-distance, frequency-domain, near-infrared spectroscopy (NIRS) method to measure the optical coefficients of two-layered media and the thickness of the top layer from diffuse reflectance measurements. This method features a direct solution based on diffusion theory and an inversion procedure based on the Levenberg-Marquardt algorithm. We have validated our method through Monte Carlo simulations, experiments on tissue-like phantoms, and measurements on the forehead of three human subjects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 89 publications
(156 reference statements)
6
65
0
5
Order By: Relevance
“…Furthermore, note that the range of scattering values we studied (4 to 20 cm −1 ) is broader than that typically reported in the literature. Similarly, we (data not shown) and others 31,49 have observed that while TD or FD two-layer models enable reasonable recovery of μ a1 , μ a2 , and μ s1 0 on layered media, in contrast, μ s2 0 can only be estimated with high uncertainty due to the low sensitivity of the TPSF to this parameter.…”
Section: Assumption Of Homogeneous Scatteringsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, note that the range of scattering values we studied (4 to 20 cm −1 ) is broader than that typically reported in the literature. Similarly, we (data not shown) and others 31,49 have observed that while TD or FD two-layer models enable reasonable recovery of μ a1 , μ a2 , and μ s1 0 on layered media, in contrast, μ s2 0 can only be estimated with high uncertainty due to the low sensitivity of the TPSF to this parameter.…”
Section: Assumption Of Homogeneous Scatteringsupporting
confidence: 83%
“…30 Paralleling the TD approach, Hallacoglu et al demonstrated the improvement afforded by the FD two-layer geometry 17 with Monte Carlo and phantom data, and applied the technique to in vivo data obtained on the adult head. 31 However, in the few in vivo studies using a layered model of the adult head, 30,31 there was no validation of the retrieved brain values by complementary modalities. More generally, the performances of the twolayer analytical methods have only been assessed through simulations or phantom measurements on simple two-layer slab geometries and not on realistic head structures.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, the thicknesses of the scalp and skull could be obtained from medical images or possibly measured directly using ultrasound. Alternately, the total scalp/skull thickness could be included as an additional fitting parameter, similar to an approach proposed for measuring cerebral oxygenation by multi-distance frequencydomain NIRS [43]. This would likely require more SDDs than used in the current study and careful attention to the shortest SDD in order to avoid violating the Siegert relationship [44].…”
Section: Discussionmentioning
confidence: 99%
“…Monte Carlo) were used. The local approach has been also explored by Hallacoglu et al [27] with a frequencydomain setup. The added value of this work, besides the higher number of volunteers involved, is the application of the different experimental techniques to the same subjects.…”
Section: Introductionmentioning
confidence: 99%